The Microbiota Protects against Ischemia/Reperfusion-Induced Intestinal Injury through Nucleotide-Binding Oligomerization Domain-Containing Protein 2 (NOD2) Signaling - Perez-Chanona, Ernesto (American Society for Investigative Pathology, 2014)
Nucleotide-binding oligomerization domain-containing protein 2 (NOD2), an intracellular pattern recognition receptor, induces autophagy on detection of muramyl dipeptide (MDP), a component of microbial cell walls. The role of bacteria and NOD2 signaling toward ischemia/reperfusion (I/R)–induced intestinal injury response is unknown. Herein, we report that I/R-induced intestinal injury in germ-free (GF) C57BL/6 wild-type (WT) mice is worse than in conventionally derived mice. More important, microbiota-mediated protection against I/R-induced intestinal injury is abrogated in conventionally derived Nod2(−/−) mice and GF Nod2(−/−) mice. Also, WT mice raised in specific pathogen-free (SPF) conditions fared better against I/R-induced injury than SPF Nod2(−/−) mice. Moreover, SPF WT mice i.p. administered 10 mg/kg MDP were protected against injury compared with mice administered the inactive enantiomer, l-MDP, an effect lost in Nod2(−/−) mice. However, MDP administration failed to protect GF mice from I/R-induced intestinal injury compared with control, a phenomenon correlating with undetectable Nod2 mRNA level in the epithelium of GF mice. More important, the autophagy-inducer rapamycin protected Nod2(−/−) mice against I/R-induced injury and increased the levels of LC3(+) puncta in injured tissue of Nod2(−/−) mice. These findings demonstrate that NOD2 protects against I/R and promotes wound healing, likely through the induction of the autophagy response.